Gold Price, Inflation, and Dollar Exchange Rate: The Case of Gold Investment in Indonesia - Rahmansyah, Ilyas Chaidir; Rani, Lina Nugraha (The Indonesian Capital Market Review, 2021)
This paper aims to investigate the relationship between gold price, inflation and the dollar exchange rate on gold stock price of PT Aneka Tambang Indonesia. The ARDL time series model is used in the study involving PT Aneka Tambang Indonesia from December 2016 to November 2019. The findings show the price of gold doesn’t have a significant effect on the gold stock price while dollar exchange rate and inflation have a negative effect on the short and long term of the gold stock price of PT Aneka Tambang Indonesia.